Innovative Рotential of the New Economy Agents - Denis Strebkov (Foresight and STI Governance)
Information and knowledge have become critical production resources in the “new economy”. The key focus is made on the workers of the new epoch as those who are concerned about the results of their labour and capable of self-development, possess entrepreneurial skills and cutting-edge tools, as well as means of communication and cooperation. They tend to be autonomous and independent and opt to freelance employment or setting up their own small businesses.On the one hand, businessmen and freelancers have a number of common features which distinguish them from traditional “wage and salary” employees, but on the other — there are certain differences connected with the organization of labour processes, communication skills and willingness to work in a team.